Isolation and culture exploration of Anas platyrhynchos amniotic fluid stem cells in vitro - Ning, Mingming; Wu, Yangnan; Ji, Meng; Guan, Weijun (Journal of Advanced Veterinary and Animal Research, 2017)
Objective: This research was designed to establish the system of isolation and culture of Anas platyrhynchos (duck) amniotic fluid stem cells (DAFSCs), and to explore its biological characteristics and differentiation ability in vitro. Material and methods: Main experimental reagents contained L-DMEM, fetal bovine serum, chicken serum, EGF, bFGF, L-glutamine, trypsin, rabbit anti-chicken CD44, CD73, CD105, nanog and SSEA-4 (Abcam, USA), FITC conjugated goat anti-rabbit secondary antibody IgG, DAPI, Trizol, inverse transcription kit, Propidium iodide, IBMX, INS, dexamethasone and indometacin. Cultivation system included L-DMEM with 10% FBS, 5% chicken serum, EGF 10 ng/mL, bFGF 10 ng/mL and 1% L-glutamine, and was cultured under 37°C, 5% CO2 and saturated humidity. Immunofluorescent detection is used to detect cell surface markers, while RT-PCR was used to detect related gene expression. Cell cycle was detected with Flow Cytometer and was analyzed by ModFitLT 2.0, induced differentiation, and Oil Red O staining. Results: More DAFSCs were gained via super-centrifugation and thermoelectric methods cost effectively. DAFSCs could go down to the future generation at passage 23(P23). CD44, CD73, CD105 and SSEA-4 were detected as positive with immunofluorescence histochemistry. GAPDH, GDNF, rex1 and JAG1 were detected as positive with RT-PCR. Cell cycle was detected on flow cytometer. Tentative exploration of differentiation ability that DAFSCs could be induced into adipocyte in vitro. Conclusion: DAFSCs can be isolated from matrix that have strong self-renewal capacity in vitro. DAFSCs can be induced into adipocyte in vitro. These testify that DAFSCs can be an ideal seeded cells having potentials for preservation and utilization of rare genetic resources. http://doi.org/10.5455/javar.2017.d200 XML PubReader